The effect of playing violent videogames and gender on aggression among first year students in Iloilo National High School - Balicanta, Alexander John F .; Cacho, Charlotte J. . (2002.)
The study was conducted to determine the effects of playing violent videogames and gender on aggression among first year high school students. The experiment design utilized two treatment groups and two control groups. The four groups consisted of (1) males who played the violent videogame; (2) females who played the violent videogame; (3) males who played the nonviolent videogame; and (4) females who played the nonviolent videogame., In this aggression was measured using the Direct and Indirect Aggression Scales (DIAS). The DIAS consists of 42 items that measure physical, vrbal and indirect aggression. Prior to the administration of the DIAS , the participants were first asked play videogames. The group were assigned to play a violent videogame and other two groups played the nonviolent games. The participants' scores in the DIAS was computed and analyzed using the two-way analysis of variance (ANOVA) with interaction. this is done to show if variables type of videogame played and gender significantly affects aggression among adolescents. The two-way ANOVA with interaction yielded three computed values of F. Results show that there is a significant F-ratio on the variable type of videogame played. The obtained F is 5.45, and an F of 4.26 is required at the 0.05 level with 1 and 27 df. Since 5.45 is greater than 4.26, the null hypothesis is rejected. Thus, the conclusion that type of videogame played has a significant effect ob aggression among first year high schooll students.l However, the F. -ratio derived for variable gender, was not significant. The obtained F is 3.59, and an F of 4.26 is required at 0.05 level with 1 and 27 df. Since the value of F is less than 4.26, the null hypothesis on gender is accepted. Thus gender has no significant effect on agression among first year high school students. The F ratio derived for the interaction of the two variables is also not significant. The computed value of F, which is only0.297, is less than 4.26. The null hypothesis, thus, is rejected. This leads to the conclusion that type of videogame played and gender do not interact to affect aggression.
BA Psychology-Management and BA Psychology
Keywords: Video games -- Case studies